2012
DOI: 10.1007/s10853-012-6654-1
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional nanostructured PANI/MnO x porous microsphere and its capacitive performance

Abstract: Three-dimensional nanostructured polyaniline (PANI) and manganese oxide (MnO x ) composite porous microspheres were prepared by oxidizing aniline with KMnO 4 under interfacial chemical synthesis with 4-aminothiophenol (4-ATP) as the structure-directing agent on the Au substrate. Surface morphology and chemical composition of PANI/MnO x microsphere were characterized by scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction, thermo gravimetric-differential thermal analysis, and Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 51 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…On the basis of this approach, the development of conducting nanocomposites received significant attention; various metal oxides that have been reported, such as Fe 3 O 4 , TiO 2 , MnO 2 , NiO, ZnO, and SnO 2 , can improve the capacitance of PANI-based supercapacitors and also their environment friendliness. Huo et al [23] has reported that the specific capacitance of the 3D nanostructured PANI-MnO x porous microspheres exhibited a maximum value of 828 F g −1 at current density of 2 mA cm −2 . Chitosan-zinc oxide (ZnO)/ polyaniline (CS-ZnO/PANI) ternary nanocomposites had been successfully synthesized by Pandiselvi K. [24]; the mesoporous CS 0.12 -ZnO 2.5 /PANI electrode yields larger specific capacitance of 587.15 F g −1 than the corresponding PANI-ZnO electrode, and the capacitance retention is 80 % after 1000 charge/discharge cycles at 175 mA cm −2 current density.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of this approach, the development of conducting nanocomposites received significant attention; various metal oxides that have been reported, such as Fe 3 O 4 , TiO 2 , MnO 2 , NiO, ZnO, and SnO 2 , can improve the capacitance of PANI-based supercapacitors and also their environment friendliness. Huo et al [23] has reported that the specific capacitance of the 3D nanostructured PANI-MnO x porous microspheres exhibited a maximum value of 828 F g −1 at current density of 2 mA cm −2 . Chitosan-zinc oxide (ZnO)/ polyaniline (CS-ZnO/PANI) ternary nanocomposites had been successfully synthesized by Pandiselvi K. [24]; the mesoporous CS 0.12 -ZnO 2.5 /PANI electrode yields larger specific capacitance of 587.15 F g −1 than the corresponding PANI-ZnO electrode, and the capacitance retention is 80 % after 1000 charge/discharge cycles at 175 mA cm −2 current density.…”
Section: Introductionmentioning
confidence: 99%
“…Since the capability of electrode materials is significantly influenced by its surface area and morphology, the electrode material with a high surface area and a uniform, ordered pore network of nanometer dimension would be expected to exhibit superior performance in an electrochemical capacitors system. As we have synthesized the 3D nanostructured PANI-MnO x porous microspheres by oxidizing aniline with KMnO 4 under interfacial chemical synthesis with 4-aminothiophenol (4-ATP) as the structure-directing agent on the Au substrate [8]. So in this paper we prepared PANI/Ni(OH) 2 by oxidizing aniline with (NH 4 ) 2 S 2 O 8 under interfacial chemical synthesis with 4-aminothiophenol (4-ATP) as the structure-directing agent on the Au substrate.…”
Section: Introductionmentioning
confidence: 99%